Urolithin A Attenuates Diabetes‐Associated Cognitive Impairment by Ameliorating Intestinal Barrier Dysfunction via N‐glycan Biosynthesis Pathway. Issue 9 (1st March 2022) - Xiao, Yao; Li, Kailin; Bian, Ji; Liu, Hang; Zhai, Xiaotong; El‐Omar, Emad; Han, Lin; Gong, Lan; Wang, Min
Abstract : Scope: This study aims to investigate the effect of Urolithin A (UA) on diabetes‐associated cognitive impairment in type 2 diabetes mellitus (T2DM) mouse model induced by high‐fat diet (HFD) and streptozotocin (STZ). Methods and Results: The UA‐treated T2DM mice display an attenuated cognitive impairment as well as reduced levels of metabolic endotoxemia and proinflammatory cytokines in serum. A systemic restraint of gut/brain inflammation in UA‐treated T2DM mice is also observed as the downregulation of TLR4 and Myd88 in colon along with the inhibition of GFAP, Iba‐1, NLRP3, and inflammation‐related genes in brain. Moreover, UA ameliorates gut barrier dysfunction by upregulating tight‐junction proteins levels. Furthermore, UA restores the hyperglycemia‐mediated downregulation of genes involved in N‐glycan biosynthesis both in vivo and in vitro, which plays a crucial role in barrier integrity. Although UA shares similar beneficial effects on diabetes with metformin, unlike metformin, the effect of UA is independent of gut microbiome and short chain fatty acids. Taken together, these data suggest that feeding UA can attenuate diabetes‐associated cognitive impairment by ameliorating systemic inflammation and intestinal barrier dysfunction via N‐glycan biosynthesis pathway. The study implies UA as a potential novel pharmaceutic target for diabetes therapy via manipulating gut‐brain axis and N‐glycan metabolism. Abstract : Hyperglycemia in type 2 diabetes mellitus (T2DM) mice disrupts the intestinal barrier integrity by downregulating N‐glycan biosynthesis pathway which is GLUT2‐dependent, leading to systemic inflammation and cognitive impairment. Urolithin A restors the suppressed N‐glycan biosynthesis in T2DM mice, so that it ameliorates the gut barrier disruption to inhibit the systemic inflammation and to attenuate diabetes‐associated cognitive impairment.